Non - relativistic bose gas in curved background - Debir, Birses. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
In this thesis we focus on the Bose-Einstein Condensation of a pure Bose gas con ned in a box placed near the horizon. Then, we formulate the nite size e ects in the limit m ! 0. We look for the number of excited particles, as well as free energy and entropy. During these processes, we used the Heat kernel expansion and the Mellin Barnes transform.
Keywords: Bose-Einstein gas.; Bose-Einstein condensation.